THE INFLUENCE OF FINANCIAL LITERACY AND PROMOTION LEVEL ON THE INTEREST IN USING ISLAMIC BANK PRODUCTS IN STUDENTS OF UIN SUNAN GUNUNG DJATI BANDUNG - Yumni Alfiah Rihadatulaisy; Anindhyta Putri Trisyanti (UIN Sunan Gunung Djati Bandung, 2023)
AbstractThis research was motivated by the significant use of Islamic bank products for UIN Sunan Gunung Djati Bandung students. This paper aims to determine the influence of financial literacy and promotion on interest in becoming a Sharia bank customer for UIN Sunan Gunung Djati Bandung students. The use of methods used in this study is quantitative research methods and surveys. The population in this study was 29,350 students of UIN Sunan Gunung Djati Bandung , and a sample of 88 respondents was obtained. The sampling technique uses clusters. Data collection method by questionnaire. The results revealed that the level of Islamic financial literacy had a significant value of 0.000 < 0.05 and had a positive and significant effect on public interest in saving at Islamic banks. In contrast, promotions of 0.061 > 0.05 so that it had no effect and was not compelling to people's interest in saving at Islamic banks.Keywords: Financial Literacy, Promotion, Interest, and Islamic Bank.